THE IMPACT OF GENDER REPRESENTATION ON GOVERNANCE SYSTEM OF SOUTH SUDAN - Dr. Alier,; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Women account for over 60% of the population in South Sudan. This is not a force of nature but a direct result of over 39 years of conflict since Sudan’s Independence. Years of conflict has not only  deprived women of their dependents - husbands and sons, but the disturbing and conventional post-war society coupled with discriminatory cultural traditions and miserable poverty undermines the promotion of equal rights and the ability for women to actively participate in the development of the new nation. The kind of traits that are typically associated with inferior leadership, such as being emotional, sensitive, dependent on others, are recast as legitimate ways of operating in the leadership realm. Again here, we can find philosophical support for including these ways of being in the world in our conception of valuable leadership.The sample size refers to the number of units that are chosen from gathered population. The sample size is calculated using the questionnaire and interview where Yemen Taro 1970s Formula was applied. 50 samples out of 100 target population was taken. In the finding result, majority of the respondents agreed and believed that representation of women in the national affairs projected gender equality and it can ensure effective development of a country. Because gender plays great roles in peace building particularly in South Sudan were entire population is traumatized by political instability which created rooms to inter-states, communal, tribal conflicts across the nation. So according to according to finding, gender has very significant roles in peace building and national development as well. In conclusion, the majority of the respondents believed that there are challenges facing women representation in governance even though government effort to equal participation.